Constructing a System to Monitor and Control Indoor Environment - Saritha, Banala; Chitti, Sridevi; Thirupathi, V. (International Journal of Engineering and Technology, 2018)
After twenty years of progress, the IoT is very much used in the real scene, which incredibly encourages people's work and lives. As individuals who pay special attention to ecological quality, the use of the Internet of Things in the observation and control of indoor conditions has become a vital branch. In this paper, we tend to an offer of intellectual answers for the administration of computer rooms following the concentration of the main advances of the Internet of Things. To obtain ecological data the frame uses sensors, thanks to the RPi procedure, the controllers will make a versatile reaction, for example, convert the live transmission conditioner, alert customers. Research shows that the framework can be a decent response to the backlog of administration of the current room, especially the school's computer room, and gives another application to the Internet of Things.Â Â Â